An Infant with Infected Cephalohematoma - Shrestha, Shodip; Pokhrel, Bibesh; Thapa, Amit (Nepal Journal of Neuroscience, 2020)
Cephalohematoma is a benign medical condition affecting 1 to 2% of all live births, which resolves spontaneously in most of the cases. Infected cephalohematomas are very rare and serious as they can cause sepsis, osteomyelitis and meningitis. We report a case of 40 days male who presented to our outpatient clinic with ruptured scalp swelling. Deep seated scalp abscess was incised and drained. Culture proved E.Coli infection which was managed with intravenous antibiotics for 5 days during the hospital stay and was later discharged on oral antibiotics. The wound completely healed with no evidence of residual abscess on 1-week follow-up. Infected cephalohematoma has good prognosis if appropriately drained and managed on culture guided antibiotics.